DE-RADICALIZATION AND DISENGAGEMENT FROM EXTREMISM: AVAILABLE POLICY OPTIONS FOR PAKISTAN (Journal of Contemporary Studies, 2012)
AbstractThis research paper attempts to propose a creative and non-conventional strategy based on ‘De-radicalization, Disengagement, and Rehabilitation (DDR)’ initiatives to deal with extremism victimizing Pakistan by radical germination. Criticality of extremism-affected communities has given birth to ingenious modes in tackling radicalization, since solely resorting to repressive hardcore military and muscular means may actually cause more problems. The trends of extremism in the world commonly identify rigid intellectual propellants behind the drawing a lesson that the spread of rotten intellectualism can solely be defeated by strategic doses of vital intellect alone and not by explosives. The DDR programming can significantly shrink the supply and demand of the militants. Tracing conceptual understanding of deradicalization and disengagement by upholding the significance of soft power strategy through DDR engineering, this research paper analyses contemporary approaches to de-radicalization; identifies phenomenal routes and roots to de-radicalization and disengagement; presents extremism and its intricacies in Pakistan; and finally makes policy recommendations for de-radicalizing and demobilizing the extremist groups.